2018
DOI: 10.1111/1749-4877.12264
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting a readily available but hard to digest resource: A review of exudativorous mammals identified thus far and how they cope in captivity

Abstract: Gum is a widely available carbohydrate, composed mainly of non-digestible structural carbohydrates. No mammalian enzymes can digest gum; therefore, a mammal ingesting gum must rely on microbial fermentation to access the energy it possesses. Gums are relatively nutrient poor. Despite this, some mammals have evolved to exploit this food resource. We aim to review the literature for all mammal species which have been recorded to ingest gum, whether quantified or not, and discuss this in the context of their evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 116 publications
1
30
0
Order By: Relevance
“…The GMC of captive and translocated marmosets shows similarity to certain aspects of the GMC of human GI diseases associated with gut microbiome dysbiosis [7,18,73,74]. Crohn's Disease (CD)…”
Section: Captive Marmoset Gmc Mirrors Aspects Of Human Gi Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…The GMC of captive and translocated marmosets shows similarity to certain aspects of the GMC of human GI diseases associated with gut microbiome dysbiosis [7,18,73,74]. Crohn's Disease (CD)…”
Section: Captive Marmoset Gmc Mirrors Aspects Of Human Gi Distressmentioning
confidence: 99%
“…A number of mammals are exudivorous [16], particularly primates [18], but their gut microibome remains less studied relative to other mammals. However, the Brazilian Callithrix marmosets, obligate NHP exudivores, are excellent models to improve our understanding of exudivore gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…However, Brack and Rothe () found that such a high level of protein may not be required but rather, the high 25% protein requirement for this species may have stemmed from fear of MWS. Cabana et al () compiled the chemical information of gums eaten by wild exudativorous mammals, most notoriously marmosets and slow lorises ( Nycticebus spp.). The average crude protein (dry matter) concentration of tree gums is 4.5% and pod gums (more often ingested by tamarins rather than marmosets) is 7.4% (Cabana, Dierenfeld, Wirdateti, Donati, & Nekaris, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both are expected to be high in magnesium, with insects also being higher in potassium and zinc (Finke & Oonincx, ). However, with less than 30% of foraging time being spent on insects (Cabana et al, ), the magnesium and zinc content of wild insects would be somewhat diluted by the ingestion of fruits, plant parts, and gum. This is necessary to balance the nutrient concentrations to acceptable amounts, as a diet too high in insects (or concentrates) may have inappropriate concentrations of certain nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation